2010
DOI: 10.1002/ptr.3317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coumestrol administration to pregnant and lactating mice on intestinal alkaline phosphatase activity

Abstract: The present study was conducted to clarify the effects of coumestrol administration on Ca metabolism during pregnancy and in lactating mice. From 6.5 to 16.5 days post coitus (dpc), pregnant mice were administered coumestrol at 200 µg/kg body weight/day. The duodenum, jejunum and blood samples were obtained at 17.5 dpc or 10 days after parturition (dap). Coumestrol administration decreased alkaline phosphatase (ALP) activity and mRNA expression of IAP and estrogen responsive genes, c-fos and vascular endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…2003). In previous studies (Kirihata et al . 2008, 2011), coumestrol administration at 200 µg/kg body weight/day during pregnancy caused a decrease in IALP activity and mRNA expression of IALP, c‐fos and VEGF in the duodenum of pregnant mice, although serum Ca was not affected.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…2003). In previous studies (Kirihata et al . 2008, 2011), coumestrol administration at 200 µg/kg body weight/day during pregnancy caused a decrease in IALP activity and mRNA expression of IALP, c‐fos and VEGF in the duodenum of pregnant mice, although serum Ca was not affected.…”
Section: Discussionmentioning
confidence: 85%
“…2006). However, our previous studies (Kirihata et al . 2008, 2011) showed that coumestrol administration at 200 µg/kg body weight/day during pregnancy decreased messenger RNA (mRNA) expression of IALP and estrogen responsive genes, c‐fos and vascular endothelial growth factor (VEGF), and the activity of IALP in the duodenum and jejunum of mice at 16.5 days post coitus (dpc) and 1 day after birth.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…AAA) flour both were found to decrease colonic AP activity in a rat model of colitis . Coumestrol, a phytoestrogen known to regulate intestinal calcium absorption, was found to inhibit IAP gene expression and enzyme activity, although differential regulation was evident in the duodenum and the jejunum in neonatal pups and lasted until 10 days postparturition . It was suggested that estrogen receptor‐alpha (ER‐α) may be involved in this transient inhibition.…”
Section: Dietary Modulation Of Iap: An Updatementioning
confidence: 99%
“…This corresponds to about 458–570 µg/kg body weight/day on the average body weight of Japanese adults. Based on less than half this limit for isoflavone intake, we previously examined the effects of coumestrol on Ca metabolism in pregnant mice given 200 µg/kg body weight/day and showed that coumestrol administration decreased the messenger RNA (mRNA) expression of IALP and the activity of IALP in the duodenum of mice at 16.5 days post coitus (dpc) and 1 day after birth (dap) (Kirihata et al . 2008, 2011).…”
Section: Introductionmentioning
confidence: 99%